Boerhaave's syndrome – tension hydropneumothorax and rapidly developing hydropneumothorax: two radiographic clues in one case. Issue 4 (5th May 2016) - Nguyen Ho, Lam; Tran Van, Ngoc; Le, Thuong Vu
Abstract: Boerhaave's syndrome is a rare and severe condition with high mortality partly because of its atypical presentation resulting in delayed diagnosis and management. Diagnostic clues play an important role in the approach to this syndrome. Here, we report a 48 year‐old male patient hospitalized with fever and left chest pain radiating into the interscapular area. Two chest radiographs undertaken 22 h apart showed a rapidly developing tension hydropneumothorax. The amylase level in the pleural fluid was high. The fluid in the chest tube turned bluish after the patient drank methylene blue. The diagnosis of Boerhaave's syndrome was suspected based on the aforementioned clinical clues and confirmed at the operation. The patient recovered completely with the use of antibiotics and surgical treatment. In this case, we describe key findings on chest radiographs that are useful in diagnosing Boerhaave's syndrome. Abstract : We report a 48‐year‐old male patient hospitalized with fever and left chest pain radiating into the interscapular area. Two chest radiographs undertaken 22 h apart showed a rapidly developing tension hydropneumothorax. The diagnosis of Boerhaave's syndrome was suspected and confirmed at the operation. In this case, we describe key findings on chest radiographs that are useful in diagnosing Boerhaave's syndrome.